Sodium intake associated with meat product consumption in Serbia. (September 2019) - Jankovic, S; Nikolic, D; Djinovic-Stojanovic, J; Radicevic, T; Stefanovic, S; Spiric, D; Jovanovic, J
Abstract: Meat and meat products are an important part of the human diet in Serbia. They are important because of their desirable taste, high nutritional value, variety of the products, traditional considerations etc. Our study addresses sodium levels in some of the most commonly consumed meat products from the Serbian market (cooked sausages, dry fermented sausages, smoked meat products, canned meats and pates). Sodium content was determined using ICP-MS. The highest sodium level was established in dry fermented sausages, and the lowest content was measured in pate. No significant differences were seen in sodium levels between cooked sausages, smoked meat products and canned meats. The mean sodium level of all analysed meat products was 11.8 g/kg. According to average intake of meat products in Serbia (54.7 g/day) and the measured sodium levels, consuming these meat products could contribute up to 26.9% of sodium daily requirements. This could pose a risk to human health considering the already high sodium intake through adding salt to food and consumption of various processed foods. Generally, the results obtained suggest reducing salt levels in meat products and as well as in diet in general.